IMPOR LIMBAH ELEKTRONIK (E-WASTE) NIGERIA DARI INGGRIS 2005-2009 - HS, Khoirul Annisak; Jamaan, Ahmad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Nigeria is a poor country with low income for the country and the people, through the case of electronic waste that happen gives opportunity for Nigeria and its people. The purpose of this study is to know motive nigeria import of electronic waste from the UK. Although there has been international regulations that of the Basel Convention, with a focus on issues of environmental loss and the profit motive.This study used qualitative methods to describe the phenomenon of this case. The data sources are from books, journals, reports and documents, theses, websites. This study used theory is Rational choice, political economy approach.Finally, this paper shows that the import of electronic waste that provides economic benefits that contribute to the economy of Nigeria national budget, the social benefits of job opportunities for the people, who have low skills, and cooperative relations trade of electronic waste that open access to the resource potential. While environmental losses, the health of the workers and those involved in it.Key word: Convensi Basel, E-Waste, Export, Import, Recycling.